Efetivação da liberdade de expressão e de imprensa perante o ordenamento jurídico brasileiro e sua transformação diante das novas mídias de comunicação - Vieira, Luis Fernando Ribeiro Serpa Fernandes (2022)
Freedom of expression and freedom of the press are important guarantees present in the Federal Constitution of 1988, being still transformed with the reality of the new social media. To understand this, we first sought to analyze how these prerogatives were historically developed in an international context in the field of Human Rights, as well as the way in which the Brazilian Constitutions themselves were treating these rights in their text, which was greatly influenced by the context history of the validity of each one, until reaching the 1988 document. Subsequently, we sought to demonstrate how the integration of these rights is carried out in the Brazilian constitutional system, in addition to the understanding, based on the principle of proportionality, of how to solve when there is a conflict between fundamental rights in a specific situation. In addition, the objective was to understand the evolution of the understanding of the national judiciary regarding freedom of the press, as well as to understand the current effectiveness of this freedom in the Brazilian context. Finally, it was visualized to observe the way in which the rights of the personality behave in the face of freedom of the press and expression, as well as the way in which the new social media impact the reality of communication, thus interfering with the reality of these rights.